Bounded rational expectation: How it can affect the effectiveness of monetary rules in the open economy - Xue Dong; Patrick Minford; David Meenagh; Xiaoliang Yang (Cardiff University, Cardiff Business School, 2023)
Since the channel for agents' expectations matters for the effectiveness of monetary policies, it is crucial for policy-makers to assess the degree to which economic agents are boundedly rational and understand how the bounded rationality affects the monetary rules in stabilising the economy. We investigate the empirical evidence for the bounded rationality in a small open economy model of the UK, and compare the results with those for the conventional rational expectations model. Overall, comparing the estimated models favours the bounded rationality framework. The results show that bounded rationality model helps to explain the hump-shaped dynamics of real exchange rate following monetary shocks, while the rational expectations model cannot. Also, we find that the exchange rate channel in the bounded rationality enlarges the effects of foreign mark-up shock, policymakers should send stronger signals over its target to the economics agents to combat the inflation. So the bounded rationality that can be found in the data still leaves scope for the forward guidance channel to work strongly enough to be exploited by policymakers.
Keywords: E52; E70; F41; C51; F31; 330; bounded rationality; monetary policy; small open economy; exchange rate channel